Moral Values in the Movie Script The Breadwinner (2017) by Anita Doron - Intan Putri Nurullia Jabar Rahim; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
This research discussed moral values in the movie script by Anita Doron, an award-winning Canadian-Hungarian writer. The aims of the research were to find out the types of moral values and the impact of moral values contained in The Breadwinner movie script to see how humans act as humans. The qualitative descriptive method was used in this research to explain gaining data through a sociological approach. The theory of Hornby was employed to analyze the types of moral values and to see what moral values are, and the theory of Thomas Lickona was used to analyze the impact. Moral values are dominant in the Breadwinner movie script, and the most dominant of all types was courage. The result showed that there were 8 of the 11 types of moral values found in the movie script of The Breadwinner namely courage, humbleness, honesty, sympathy to others, cooperative, thankfulness, kind-hearted, and love and affection. In The movie script, it was also found that there were only 4 types of impact moral values, namely honesty, courage, honor and love and affection based on Thomas Lickona's theory.